PREVALENSI PRADIABETES PADA MAHASISWA AKPER KESDAM IV/DIPONEGORO: PREVALENCE OF PREDIABETES IN STUDENTS OF AKPER KESDAM IV/DIPONEGORO - ainnur rahmanti; Margiyati Margiyati; Intan Alawiyah; Dina Selviana (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2020)
Prediabetes will become a widespread health problem and have a serious impact (emerging epidemic. Prediabetes condition is a condition of a person before suffering from diabetes mellitus which is characterized by an increase in hyperglycemic status above the normal laboratory threshold value, but does not increase in diabetics. The prevalence of diabetes increases every year, data shows 5-14% of prediabetic conditions will become diabetic every year. There has been a shift in the age of people with diabetes, from previously a disease that affects the elderly, to a disease that attacks at a young age. If young age is identical with type 1 diabetes, now individuals are the group of young adults also suffers from type 2 diabetes mellitus. Likewise with prediabetes, the number of young adults who experience prediabetes is increasing every year. Students are a group of young adults who have a combination of risk factors for hyperglycemia. Life such as reduced physical activity because it is not necessary to exercise regularly for a certain period of time such as in the previous education period makes students have a high risk of developing prediabetes conditions. Efforts to detect non-communicable diseases early in the community are expected to help reduce and prevent the incidence of prediabetes that occurs in Kesdam IV/Diponegoro Akper students.